Beef Cattle Farming Area Planning Based on LQ and GIS Analysis in West Kutai Regency - Dede Aprylasari; Apdila Safitri; Yoga Toyibulah (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Beef cattle are a strategic commodity in supporting animal food security and strengthening the regional economy.West Kutai Regency has significant potential for beef cattle development, but is not yet supported by targeted, data-driven livestock planning. This study aims to identify base and non-base areas for beef cattle and map priority zoning for beef cattle center development through the integration of Location Quotient (LQ) and Geographic Information Sistem (GIS) analysis. The study was conducted from April to October 2025 using primary data from field observations and secondary data from relevant agencies. LQ analysis was employed to assess the level of specialization within the beef cattle population at the sub-district level, while GIS spatial analysis was utilized to integrate the LQ results with information on land use and regional accessibility networks. The results showed that of the 16 sub-districts, five are base areas (LQ > 1): Long Iram, Sekolaq Darat, Linggang Bigung, Nyuatan, and Penyinggahan, with Long Iram having the highest LQ value (2.79). The integration of LQ results and spatial modeling resulted in a priority zoning map that highlighted the primary concentration of beef cattle development in areas with high livestock populations, adequate accessibility, and available cultivation space. This study emphasizes the significance of quantitative and spatial approaches in livestock spatial planning, thereby supporting the development of sustainable beef cattle centers in West Kutai Regency.